Institutional trajectories of youths in the state protection system in Colombia - Vargas Prado, Ingrid Daniela; Ortegón Machado, David Stevens (Revista Colombiana de Ciencias Sociales, 2026)
The present article aims to analyze the characteristics of institutional life in young people under residential care in the district of Cali who lost parental care between 2022 and 2023, from the perspective of their individual life trajectories. Key concepts such as life course, trajectories, and institutionalization are revisited, which helped to highlight assumptions that institutionalization generates effects on the individual’s development. In this way, it was possible to show that in young adults who grew up within the Colombian Protection System, it is possible to recognize an existing tension between their level of autonomy, institutional demands, and the possibility of a world outside that is often unknown in its functioning, an aspect that poses challenges to the individual in their exercise of citizenship.